2013
DOI: 10.2298/vsp110905041d
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of amifostine in protection against doxorubicin-induced acute cardiotoxic effects in rats

Abstract: AMI provided a significant protection against DOX-induced acute cardiotoxic effects in rats. This finding implies its potential to be a successful cardioprotector in patients treated with DOX due to malignant diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Injury to these organs has been attributed to oxidative stress induced by the reactive intermediate doxorubicin semiquinone, formed from DXR [14]. Thus, several antioxidants have been tested in studies to alleviate the toxic effects of DXR [14,15]. In this study, we assessed the efficacy of RA, which has anti-inflammatory, antimicrobial and antioxidant effects on DXR-induced testicular damage [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injury to these organs has been attributed to oxidative stress induced by the reactive intermediate doxorubicin semiquinone, formed from DXR [14]. Thus, several antioxidants have been tested in studies to alleviate the toxic effects of DXR [14,15]. In this study, we assessed the efficacy of RA, which has anti-inflammatory, antimicrobial and antioxidant effects on DXR-induced testicular damage [7].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dragojevic-Simic et al [15 ]explored the efficacy of amifostine, a broad-spectrum cytoprotector, on the cardiotoxic effects of DXR and showed that it had a cardioprotective effect in DXR-induced injury. Shivakumar et al [14 ]assessed the impact of vitamin E on tissue damage caused by DXR in the heart, kidney, liver and testes.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous experimental models concerning these subjects, which showed DOX-induced bone marrow toxicity, cardiotoxicity, hepatotoxicity, nephrotoxicity, and toxic effects on the GI tract (GIT), reproductive system, and nervous system [4,9,10,11,12,13,14,15]. DOX acts as a strong inhibitor of DNA duplication and transcription, with the most obvious consequences on tissues with strong proliferative potential, such as bone marrow, GIT, and the reproductive system.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, DOX, by virtue of its quinone group, generates free radicals in vitro and in vivo, which is significantly stimulated by its interaction with iron. Moreover, oxidative stress, apoptosis, and inflammation can be taken as possible mechanisms of DOX multiple-organ toxicity, such as cardiotoxicity on the first place [5,12,15,16,17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation